Corporate Identity Bougenvilleee Project - Putri Ananda; Hendra Afriwan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Bougenvilleee Project is a company that offers printing, convection and screen printing services such as printing invitations, flyers, mugs, t-shirts and other merchandise for organizations/communities/companies in large quantities. This company was founded by M. Arif Budiman and Marhayati in 2019, located on Jalan Kuini, Pekanbaru. The aim of this design is to make the company more professional, trustworthy and have a consistent corporate identity because the company's target market is more about the company's personal clients. Identity influences consumer shopping decisions, so identity can be a differentiator regarding consumer perceptions of the Bougenvilleee project's services from other competitors. The design method used is the 4D method, consisting of 4 stages, namely the Define, Design, Develop and Disseminate stages. The design analysis used is through SWOT analysis. The results of the Bougenvilleee Project corporate identity design in the form of this logo will be applied to the stationary office (invoice, letterhead, stamp, ID card, business card, t-shirt), then the main media in the form of the Brand Guideline and various supporting media for the company identity.